Promoting Phoenix Embroidery Surabaya Using a Commercial Website - James Leicester (Kata Kita: Journal of Language, Literature, and Teaching, 2017)
Phoenix Embroidery Surabaya (PES) is an embroidery industry that was established in 2004. It is located on Simolawang Baru 5/9, Surabaya. It started to embroider denim fabrics. This company needs new markets to fulfill its production targets. This company needs new markets to fulfill its production targets. So far, the markets of PES are garment industries have produced denim fashion for low-class people. A commercial website is a way that I use to help PES in solving its problem. A website is easy to access and can be access by everyone. This advantage can be a benefit for PES to reach many people seeing the existence of PES itself. This website is expected to reach out to garment industries not only for low-class consumers and to gain new markets especially from souvenirs and home decorations industries.